Design and evaluation of bromelain-encapsulated alginate beads reinforced with gum Arabic: Formulation, characterization, and stability in simulated gastrointestinal conditions - Methavee Peanparkdee; Phornphimon Janchai; Tanwarat Aksornsri; Pilanee Vaithanomsat (Journal of Agriculture and Food Research)
Hydrogel beads containing purified, crude extract and commercial bromelain preparations were developed using encapsulation technique with two carrier agents, sodium alginate and gum Arabic in various ratios of 2:0, 1.5:0.5 and 1:1 (w:w). Stability assessment of bromelain-loaded hydrogel beads was conducted using in vitro gastrointestinal digestion models. Beads produced with 2 % (w/v) sodium alginate (S2) and 1.5 % (w/v) sodium alginate combined with 0.5 % (w/v) of gum Arabic (SG1.5) demonstrated high production yield in a range of 90.99 %–95.92 % and loading capacity in a range of 76.03 %–76.97 %. All bead samples showed high encapsulation efficiency in a range of 93.71 %–98.49 % with spherical shapes. The formulation of 1.0 % (w/v) sodium alginate combined with 1.0 % (w/v) gum Arabic (SG1) resulted in a higher wall thickness. SEM image revealed numerous small crystals on the surface of SG1.5 and SG1, which were formed by crude extract and commercial bromelain. Crude bromelain extract-loaded beads exhibited optimal protein release across pH 3–7 at 25 °C, with enhanced release following thermal treatment. Encapsulation in SG1 resulted in the highest protein release (105.38 %) and antioxidant activity (36.41 mmol Trolox/g bead for FRAP, 6.34 mmol Trolox/g bead for ABTS) after intestinal digestion. Conversely, the encapsulated purified bromelain yielded the lowest release of protein and antioxidant activity after simulated digestion due to the structural formation between bromelain and wall materials. The hydrogel beads have potential to enhance the stability and bioaccessibility of bromelains.